2012
DOI: 10.1097/opx.0b013e318264e85a
|View full text |Cite
|
Sign up to set email alerts
|

The Berkeley Rudimentary Vision Test

Abstract: The BRVT is a simple and efficient test of spatial vision that, with 13 increments, extends the range of measurement from the limits of the letter chart up to light perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 14 publications
0
61
0
Order By: Relevance
“…During VI classification, visual acuity is currently assessed using a logMAR chart and the Berkeley Rudimentary Vision Test,10 and visual fields are assessed using Goldman, Humphrey or Octopus perimetry. We asked the panel whether they were confident that the current tests of visual acuity and visual field were appropriate for the purpose of classification.…”
Section: Resultsmentioning
confidence: 99%
“…During VI classification, visual acuity is currently assessed using a logMAR chart and the Berkeley Rudimentary Vision Test,10 and visual fields are assessed using Goldman, Humphrey or Octopus perimetry. We asked the panel whether they were confident that the current tests of visual acuity and visual field were appropriate for the purpose of classification.…”
Section: Resultsmentioning
confidence: 99%
“…Distance VA was determined both binocularly and monocularly following the procedure of Bailey et al 6. Specifically, a handheld ETDRS LogMAR letter chart was held at 4 m (2000 Series Revised, Precision Vision, La Salle, Illinois, USA), with the viewing distance reduced to 2 and 1 m if the participant could not read the largest letters on the chart.…”
Section: Methodsmentioning
confidence: 99%
“…Letter by letter scoring was used with the acuity measured in logMAR units. If the VA was too poor to be recorded using the letter chart (VA >1.60 LogMAR), the Berkeley Rudimentary Vision Test (BRVT)6 (Precision Vision, La Salle, Illinois, USA) was used. If the athlete could not see the maximum letter size (LogMAR 2.60) at the closest test distance then a standard test of light perception was performed.…”
Section: Methodsmentioning
confidence: 99%
“…Often in clinical practice Snellen charts are used while in clinical trials ETDRS charts are utilized (Falkenstein et al, 2008). Recently, Bailey et al (2012) suggested using The Berkeley Rudimentary Vision Test for low vision visual acuity testing. It consists of three pairs of hinged cards that test using single tumbling E optotypes, various grating acuity targets, and white field projection and black white discrimination.…”
Section: Introductionmentioning
confidence: 99%